PERAN PIHAK KETIGA ATAS PINJAMAN ONLINE - Natalia Yeti Puspita; Elvina Elvina; Samuel MP Hutabarat (Gloria Justitia, 2022)
Technological developments have led to borrowing and borrowing money, which was initially carried out directly, is now being carried out indirectly (online). Debtors simply enter personal data into the online loan application and must enter Emergency Contact as the party to be contacted if the Debtor cannot be contacted. Problems occur when the Creditor contacts the Emergency Contact and asks to pay all debts owed by the Debtor. The position of the legal subject who becomes the Emergency Contact is still unknown as a guarantor or not. Therefore, the author raised this thesis to explain the position of the Emergency Contact whether as a party who guarantees the debtor's debt or not, by using the writing method used is normative juridical.